Perhitungan Sumberdaya Batubara dan Permodelan Pit 2 Pada PT. Andhika Yoga Pratama (AYP), Kecamatan Pauh, Kabupaten Sarolangun, Jambi - Rahmad Febrian Ikhwal; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract.Coal is one of the minerals contained in the Indonesian energy with enormous potential, the one in Sumatra. Location IUP PT. Andhika Pratama Yoga is located in District Pauh, Sarolangun, Jambi. In an effort to determine the amount of the reserves contained in the mining permit area, then a company must carry out exploration activities, which includes observation of outcrop (outcrop descriptions, measurement strike and dip) and mapping the subsurface by observing the cutting results of drilling activity. This study of the general mengambaran thickness conditions in the study area, counting the coal reserves in the area of research until the pit design and mine layout. From the correlation between the point of drilling. Resource calculation performed using software Minescape and the method of poligons. Volume obtained for the pit reserve of 12 hectares amounted 26900.01 tons and the amount of overburden to be opened for 78177.11 tons. With striping ratio is 1: 2.906. Keywords: Coal, Coal Reserves, Overburden, Striping ratio, Minescape